Comunidad, pertenencia, extranjería El impacto de la migración laboral y mercantil de la región del Mar del Norte en Nueva España, 1550-1640 - Poggio, Eleonora (Leuven University Press, 2022)
Comunidad, pertenencia, extranjería' reveals the central role played by labour and mercantile migration from the North Sea region in the Viceroyalty of New Spain during a critical period in the formation of colonial societies. Far from being a marginal migration, as has been believed until now, the presence of northern migrants was strategic for the expansion and maintenance of the Hispanic monarchy due to their contribution of labour, technological knowledge, commercial networks, and transnational capital. From the cross-sectional analysis of the impact of this migration on the society, politics, and economy of New Spain, this work shows how it is impossible to tell the story of the Spanish empire without taking into account the role that non-Spanish Europeans played in its formation and evolution.